TINJAUAN TERHADAP PELAKSANAAN RESTRUKTURISASI KREDIT PERBANKAN - Budi Prana Prasetyo; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2021)
According to Law No.1 of 1998 regarding Banking Law, one of the functions of a bank is to channel funds to the public in the form of credit and / or in other forms. In channeling bank credit, there is always a probability that a risk may occur. The most common risk that occurs in bank credit is Non-Performing Loan (NPL). When the debtor did not meet the performance demanded in the credit agreement, then NPL will occur. The policies that are often taken to resolve the high NPL ratio is by restructuring credit structure against debtors who still have prospects for repayment and confiscate collateral objects against debtors who have no prospects for repayment. The existence of the Covid-19 outbreak has made economic conditions experience a slowdown, the Bank as one of the drivers of the economy cannot be separated from this impact. Due to Covid-19, to cope with a risk of a simultaneous increase in NPLs, OJK as the institution that has the authority in the field of regulation and supervision of banking activities issued POJK 11/2020 regarding stimulus policies in dealing with the impact of Covid-19. The policy includes determination of asset quality and credit restructuring. The stimulus policy applies to banking financial services institutions, and is aimed at debtors whose businesses are affected. From this research we can conclude; some differences in the arrangements regarding restructuring under normal circumstances and restructuring due to Covid-19, factors that hamper the implementation of restructuring.